Skrining Aktivitas Senyawa Limonen dan Turunannya dalam Menghambat Enzim MMP-2, MMP-9, Cyclin A2 pada Kanker Payudara Triple Negative melalui Molecular Docking - Qurrotul A'yun; Warsito Warsito; Elvina Dhiaul Iftitah (Postgraduate, University of Mataram, 2022)
Breast cancer is among the diseases with the highest mortality rate in women in the world. The triple negative cancer subtype with aggressiveness and metastatic ability causes the sufferer to be difficult to treat. Targeted treatment efforts of natural ingredients such as limonene and its derivatives are more profitable due to their easy excretion process.Â Screening the activity of compounds through docking specifically provides convenience in the synthesis process in the laboratory. Limonene compounds and their derivatives will be interpreted against the enzymes MMP-2 (PDB ID: 3AYU), MMP-9 (PDB ID: 4H1Q) and Cyclin A2 (PDB ID: 2V22) involved in the cellular function of triple-negative breast cancer using PyRx 9.0 software. The docking results showed that the limonelyl salicylate compound provided the best binding affinity value against the enzymes MMP-2, MMP-9, and Cyclin A2 with successive values of -7.7, -8.8, and -6.7 kcal/mol.